The Influence of Instagram Social Media Marketing on Room Sales at the Arshika Bali Sunset Road Hotel - Linge Abdul Wahab, Akbar; Hanifa Nur Fadhilla (Cita konsultindo, 2024)
This study aims to analyze the influence of Instagram Social Media Marketing on the increase in sales at Hotel Arshika Bali Sunset Road. This study uses a quantitative approach with an associative research design. It involves all hotel employees as a population. The sample was selected using non-probability sampling, especially purposive sampling. Data analysis was carried out using descriptive statistical methods. The results show that Instagram Social Media Marketing has a significant positive influence on increasing hotel sales. These findings indicate that effective Social Media Marketing implementation correlates with increased sales at the Arshika Bali Sunset Road Hotel.